Characterisation of Copper (Ii) Oxide Synthesised by Precipitation Method - Lau, Hooi Hong (2005)
In this study, copper(I1) oxide (CuO) nanocrystalline powders were successfully synthesised via precipitation method. The main advantages of the method for the material preparation are the possibility of creating very pure materials and the flexibility of the process with respect to final product quality. Synthesis parameters which were concentration of copper, concentration of precipitating agent, pH and types of precipitating agents were varied and their influence on the microstructural properties of CuO were studied. Results showed that 1.0 M of copper nitrate, Cu(NO& solution and 1.5 M of ammonium hydroxide, NH40H solution were the most suitable molarities for its given the best precipitation yield and improved microstructural properties. The calcination temperature of 623 K was chosen because thermal gravimetric analysis revealed that the precursors fully transformed to CuO at this temperature. As evidenced by X-ray diffraction analysis, all the precursors were in copper hydroxyl nitrate phase and all the calcined samples were pure CuO in 23-36 nm size with monoclinic structure. The FTlR spectra showed the incorporation of nitrate and hydroxide anions into copper cations in the precipitation process. CuO obtained from precipitation at pH 1.6 by using NH40H as precipitating agent showed the higher surface area, 8.7 m2 g-' in comparison with CuO prepared from ammonium carbonate, (NH&C03 and sodium carbonate, Na2C03. For precipitation finished at higher pH, i.e. pH 3.0 and pH 4.2, respectively, CuO synthesised from Na2C03 possessed higher surface area in comparison with CuO synthesised from NH40H and (NH4)2C03. From electron microscopy studies, tabular crystallites with elongated hexagonal morphology were observed for the CuO prepared by using NH40H. CuO precipitated from (NH4)2C03 were in platelet morphology. Granular morphology was observed for the CuO prepared from Na2CO;. Results of temperature-programmed reduction in hydrogen showed that the total amount of oxygen removed from CuO was influenced by the surface area of CuO. It was found that higher CuO surface area promised higher reducibility of CuO due to the decreasing of crystallite size.